2018
DOI: 10.24093/awej/vol9no2.18
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Humour in EFL Classrooms: Comparative Conversational Analysis Case Study

Abstract: Utilising a sequential explanatory mixed-methods approach, the current case study investigates the characteristics and frequency of the usage of verbal humour that positively or negatively affects the Saudi English as a Foreign Language (EFL) tertiary-level students across two different English language proficiency levels. The participants included 42 EFL teachers and 138 male EFL students from the English Language Institute (ELI) in King Abdulaziz University. The students were enrolled in the beginners (E101)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Norrick (2003) indicated that it is difficult to identify the differences amongst many teacher humor styles since it is often faded into each utterance in a conversation. These types have been named irony, teasing, banter, language play, jokes, riddles, and other forms (Fadel & Al-Bargi, 2018).…”
Section: Definitions Of Humormentioning
confidence: 99%
See 3 more Smart Citations
“…Norrick (2003) indicated that it is difficult to identify the differences amongst many teacher humor styles since it is often faded into each utterance in a conversation. These types have been named irony, teasing, banter, language play, jokes, riddles, and other forms (Fadel & Al-Bargi, 2018).…”
Section: Definitions Of Humormentioning
confidence: 99%
“…Irony refers to the employment of implicit or ambiguous speeches or utterances that have double meanings (Fadel & Al-Bargi, 2018). Sarcasm, a subtype of irony, is more likely to be used for aggressive purposes in speech or to harm the sentiments of its target than other simple kinds of irony.…”
Section: Ironymentioning
confidence: 99%
See 2 more Smart Citations
“…While this may appear obvious, studying the acquisition of verbal humour is less straightforward, and to date there has been less research on children's humour from a linguistic point of view than from a psychological and psychoanalytical perspective or with an experimental approach (for an overview, see Del Ré et al this issue). In L2 research, most previous studies have looked at the understanding of humour and at its close link to proficiency (Bell 2009;Fadel & Al-Bargi 2018), and while humour expression in sign languages has been looked at extensively (see Vincent-Durroux this issue), less is known about humour expression in deaf people who use an oral language. Although the researchers in this issue all employ different methodologies, and study quite distinct groups of participants, the studies all share a contrastive approach across languagescultures, and work with naturally occurring conversational data.…”
mentioning
confidence: 99%